1999
DOI: 10.1002/1529-0131(199908)42:8<1673::aid-anr16>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of increased susceptibility to apoptosis of CD4+ T cells with lymphocyte activation and activity of disease in patients with primary Sj�gren's syndrome

Abstract: Objective. To investigate whether a change in the CD95-related apoptosis of T lymphocytes might have a share in the development of the disease in patients with primary Sjögren's syndrome (SS). Methods. Two-color cytometric analysis was used to study the phenotype of freshly separated mono-nuclear cells, while Western blotting was used to detect CD95 ligand (CD95L) expression in total homogenates of isolated CD4 T lymphocytes. The ability of various subpopulations of T cells to undergo apoptosis was investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 30 publications
4
28
0
Order By: Relevance
“…The increase in T cells after ED administration of CD4 would be due to reduced CD4ϩ T cell activation, resulting in a decrease in the activation-induced death of CD4ϩ T cells, which may explain the larger relative cell numbers in the anti-CD4 mAb-treated mice than in the control IgG-treated mice. This is supported by results from a previous study (20) demonstrating increased CD4ϩ T cell apoptosis in humans with SS. Furthermore, in our preliminary experiments, we observed a decrease in annexin V-positive CD4ϩ T cells in lymph nodes from mice treated with ED administration of CD4 (data not shown).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The increase in T cells after ED administration of CD4 would be due to reduced CD4ϩ T cell activation, resulting in a decrease in the activation-induced death of CD4ϩ T cells, which may explain the larger relative cell numbers in the anti-CD4 mAb-treated mice than in the control IgG-treated mice. This is supported by results from a previous study (20) demonstrating increased CD4ϩ T cell apoptosis in humans with SS. Furthermore, in our preliminary experiments, we observed a decrease in annexin V-positive CD4ϩ T cells in lymph nodes from mice treated with ED administration of CD4 (data not shown).…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, we and other investigators (12,15) have found that patients with SS have high titers of serum anti-␣-fodrin antibody, suggesting that ␣-fodrin is a critical autoantigen for the onset or progression of human SS. Although the mechanism of autoimmune disorders in the lacrimal and salivary glands in this mouse model is still unclear, autoreactive CD4ϩ T cells are responsible for the destruction of the lacrimal and salivary glands in this model (16)(17)(18) as well as in human SS (19,20).…”
mentioning
confidence: 93%
“…Similarly to various systemic autoimmune diseases, in which altered apoptosis capability of PBMCs is characteristic and may contribute to the maintenance of the autoimmune processes (Bijl et al, 2001;Funauchi et al, 2001;Papo et al, 1998;Stummvoll et al, 2000;Zeher et al, 1999), our findings revealed the presence of activated peripheral blood T lymphocytes with impaired apoptosis, resulting in long-lived T cells peripherally in RA. This may contribute to the recruitment of these cells to the site of tissue damage and the perpetuation of the autoimmune inflammatory process.…”
Section: Szodoray Et Alsupporting
confidence: 51%
“…Because PBMCs play an important role in the pathogenesis of various systemic autoimmune diseases, such as systemic lupus erythematosus (Bijl et al, 2001;Funauchi et al, 2001;Papo et al, 1998), Sjögren's syndrome (Zeher et al, 1999), and systemic sclerosis, (Stummvoll et al, 2000), we further investigated this phenomenon in RA.…”
mentioning
confidence: 99%
“…Abu-Helu et al (2001) showed that salivary gland epithelial cell lines (SGEC) constitutively expressed more membranous Fas and intracellular FasL than controls, while Shibata et al (2002) detected Fas/FasL expression in ductal and acinar cells of SS patients but not in controls. Other studies have suggested that Fas may accelerate the apoptotic death of peripheral CD4 T cells in SS patients (Zeher et al, 1999;Ohashi et al, 1996). However, Ohlsson et al (2001) found Fas-induced epithelial cell apoptosis to be a rare event, with a frequency of less than 1% in salivary glands from 18 SS patients.…”
Section: Sjogren's Syndromementioning
confidence: 95%